2004
DOI: 10.2746/0425164044864589
|View full text |Cite
|
Sign up to set email alerts
|

Immunological response to long‐term transport stress in mature horses and effects of adaptogenic dietary supplementation as an immunomodulator

Abstract: Summary Reasons for performing study: Little information exists on the immunological effects of transport or the use of supplements to minimise transport stress. Objectives: To establish baseline ranges and evaluate immunophenotypic and functional changes associated with transport and a nutritional ‘adaptogen’ supplement. Methods: Horses received either supplement (n = 10) or placebos (n = 9) during the 30 day study. After 28 days in stalls, 12 horses (6 supplement; 6 placebo) were transported for 24 h, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
3
23
2
1
Order By: Relevance
“…It is well known that transportation can cause both tachycardia and hormonal disruption in horses (Baucus et al, 1990;Clark et al, 1993;Warren and Cuddeford, 1995;Rodiek, 2000, 2002;Stull et al, 2004). Previous studies have confirmed cardiac frequency monitoring as a valuable measure of the immunological condition (Harlow et al,1987), energy expenditure (Giovagnoli et al, 2002), and welfare for short term stressors such as those encountered during loading and transport (Minero et al, 2001;Broom et al, 2002;Honkavaara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that transportation can cause both tachycardia and hormonal disruption in horses (Baucus et al, 1990;Clark et al, 1993;Warren and Cuddeford, 1995;Rodiek, 2000, 2002;Stull et al, 2004). Previous studies have confirmed cardiac frequency monitoring as a valuable measure of the immunological condition (Harlow et al,1987), energy expenditure (Giovagnoli et al, 2002), and welfare for short term stressors such as those encountered during loading and transport (Minero et al, 2001;Broom et al, 2002;Honkavaara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Long distance horse transportation can result in substantial stress and alteration in immune function, including an acute phase response that results in impaired cell‐mediated immunity . Imported horses also have increased exposure risk to infectious respiratory pathogens, because of comingling at sales/shipping barns, quarantine facilities, and during transports.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies to determine the amount of transport stress in horses have been carried out (Leadon, 1994;Fazio and Ferlazzo, 2003;Stull et al, 2004) and thus it is well known that long-term stress (24 to 48 h) can influence a number of systems in the horse, including the immune, digestive and reproductive systems (Baucus et al, 1990a and1990b). The extent to which short transport stress influences the horse's thyroid function has not been sufficiently studied and only limited scientific data are available that demonstrate its effect on body weight (BW), rectal temperature and heart rate (HR) changes (Stull, 1999).…”
Section: Introductionmentioning
confidence: 99%